Performance Efficiency of the Indonesian Banking - Lule, Benny (JBE (Journal of Business and Economics); Volume 8 No.1, 2009 JBE UNKLAB, 2009)
This paper aims to measure and analyze the performance efficiency of the Indonesian banking listed in IDX for LQ 45 during period 2003 – 2007. The study uses Output-Oriented Malmquist Productivity Index (DEA approach) to analyze 35 panel data composed of 7 banks and 5 year periods. The findings show that the Indonesian banking is productive and efficient as a whole.  There are positive growth productivity and efficiency rate as much as 5.1 percent and 2.4 percent, respectively. However, the findings show that 29 percent of the banks are non-productive and 43 percent is inefficient ones.